KEBERTAHANAN LEKSIKON BUDAYA DALAM SENI PERTUNJUKAN SANDUR MADURA DI PONTIANAK - Sajidin Muttaqin Putra; Laurensius Salem; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe scarcity of Sandur's performing arts indicates that the performing arts have begun to be abandoned by the Madurese community. Not only that, it is now rare to find groups or training studios and Sandur Madura performance studios. This condition is the main reason for researchers to examine the survival of the lexicon in the Sandur Madura performance art in Pontianak. The method used in this research is descriptive and the forms of research used in this study are qualitative and quantitative. The data in this study are in the form of a lexicon in the Sandur Madura performance art in Pontianak. The data source in this study is the informant who is closely related to the performing arts of Sandur Madura in Pontianak City. The author uses interview techniques and survey techniques. Data collection tools that I use in the form of a recorder, interview guidelines, notebooks, and questionnaires. Based on research data, it was found sandur was carried out during gathering such as festivity, in a meeting, people died, village meetings, Eid days, and the arrival of a dignitary. There are 50 words and 5 phrases that only survive in the old age group.Keywords: Lexicon, Sandur Madura, Survival